TINJAUAN YURIDIS PERATURAN KOMISI PERSAINGAN USAHA REPUBLIK INDONESIA NOMOR 6 TAHUN 2009 TENTANG PEDOMAN PENGECUALIAN PENERAPAN UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT TERHADAP PERJANJIAN YANG BERKAITAN DENGAN WARALABA - , Dwitya Bharata Nandiwardhana, SH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is about Juridical Review of Regulation on Business competition supervisory commission of the Republic of Indonesia No. 6 Year 2009 concerning guideline the Exception Implementation of Act No. 5 Year 1999 concerning Prohibition of Monopoly Practice and Unfair Business Competition toward Agreement related to Franchise. This research aims at finding out the rationale of the issue of Commission Regulation No. 6/2009, the articles which their implementations are not in exception of Act No.5/1999 as well as the implementation of Commission Regulation No. 6/2009. This research used qualitative data analysis that is data obtained from the results of the research on literary and field research which are chosen or selected based on the quality of the truth, relevant data with problems arranged systematically and with deductive thinking method, then it is concluded to answer the problems. The rationale of the issue of Commission Regulation No. 6/2009 is the potential of monopoly practice and unfair business competition stated in articles in the agreement on franchise or actions of business performers is monopolistic and oligopolistic so it is worried that franchise business only becomes a âshieldâ for business performers especially franchisor in doing actions which are opposite to Act No. 5/1999. Commission Regulation No. 6/2009 also provides limitations of the implementation of franchise especially in the agreement on franchise between franchisor and franchisee. Provisions or clauses that are violate act No. 5/1999 such as resale price maintenance, divison of market, requirements for purchasing supply of goods and/or servise only from franchisor and non competition clause. The implementation Commission Regulation No. 6/2009 involves several parties, including Business Competition Supervisory Commission (KPPU), Ministry of Commerce, and Business Parties.